Isotopic evidence of increased societal diversification in Pre-Columbian Panama - Ashley E. Sharpe; Nicole E. Smith-Guzmán; Claudia Patricia Díaz Pérez; Luis Alberto Sánchez Herrera; Diana Carvajal-Contreras; Jason Curtis; Jonathan D. Cybulski; Benoit Desjardins; Ilean Isaza-Aizpurúa; George Kamenov; Yajaira Núñez-Cortés (PLoS ONE, 2025)
The Pre-Columbian history of Panama stands in unique contrast to the state-level societies of Mesoamerica to the north and the Andes to the south. Characterized by a network of powerful chiefdoms at the time of the Spanish arrival in the early 16 th century, paleoecological and archaeological evidence indicates that the inhabitants of the isthmus had begun practicing horticulture with early domestic plants by 7000 BCE and adopted ceramic technology around 2500 BCE, both of which were earlier than most of the North and Central American continent. The development of the sociocultural sphere of chiefdoms that arose in this region between 200 BCE – 1500 CE is still not well understood. Focusing on one of the largest sites excavated to date in Panama, Cerro Juan Díaz, this study uses isotopes (carbon, nitrogen, oxygen, and strontium) from bone and tooth enamel of 49 human individuals combined with preexisting isotopic data from nearby sites to understand the diet and mobility patterns of humans in ancient Panama. While the earlier centuries of life at Cerro Juan Díaz are marked by a consistent diet of maize and marine resources among most members of the community, by 700 CE a shift occurs where both diets and movements among individuals become highly variable. By 1150 CE, distinct isotopic differences emerge between sexes and between adults and children, revealing evidence of increasingly diverse social roles and mortuary practices. We interpret these results considering other archaeological and ethnohistoric records from the region to understand social trends that occurred in Panama throughout the 1500 years before Spanish contact.